(untitled) (American Journal of Islam and Society, 2007)
In this brilliant contribution, Timur Kuran weaves six chapters into a sound critique of the assumptions and practices of Islamic economics. In essence, he attacks the very foundation of Islamic economics, the prohibition of interest, and then extends his critique to whether Islam’s traditional redistributive instruments in achieving contemporary economic goal is feasible. The author’s intention is not simply to critique Islamic economics, but to bring the ideas espoused by the discipline into the realm of mainstream social sciences and encourage serious scholarly consideration. The first two chapters summarize the basic tenets of Islamic economics while grounding the discipline in two central claims: that existing economic systems have failed and that Islamic history proves the Islamic system’s superiority over others. Kuran dismisses the latter by revealing that modern economic problems had historical counterparts, that many concepts and methods utilized by Islamic economists originated outside the Islamic world, and that applying ancient solutions to present problems is an inadequate approach. Islamic economics’ material expression has been confined to Islamic banking, for which prohibiting interest is the sine qua non, and redistribution efforts. Profit and loss sharing techniques, namely, mudarabah and musharakah, have been derived from classical Islamic jurisprudence in order to avoid interest. These terms refer to practices whereby an individual entrusts an entrepreneur or an investor with an amount of capital that will yield a specified return. Kuran attacks these practices, asserting that they remain mechanisms for charging interest on the grounds that since modern banking is based on profit and loss sharing, these classical methods simply allow bankers to avoid using the term interest ...